Prudential Principles Notary in Making Deed Agreement Between Transplant Donor and Recipient - Sri Nurdiana Purwaningsih; Sarsintorini Putra; Anggraeni Endah K. (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Transplantation of organs in humans is one of the fastest-growing alternative treatments. Theuse of donors from non-family members is one of the considerations. Is a notarized agreement between theorgan giver and the organ recipient necessary so that problems do not occur in the future?Objective: This study’s objective was to analyze the principle precautionary in a notarized deed agreementbetween the donor and recipient transplant.Method Research: This research method uses a normative and empirical juridical approach with descriptiveanalytical and normative research specifications.Conclusion: This study found that the alleged buying and selling of kidneys leaves underhand agreements’ongoing problem. The paradigm that applies in the work of notaries is the principle of prudence in doingnotarial deeds. Prudence comes from the word prudence, which is analogically closely related to thesupervisory function management as it applies to banking. A notary caution is required to draft a transplantnotary agreement between donors and recipients so that disputes do not occur in the future.